The Influence of Human Resource Capacity on Sustainable Development in Malang City - Alhaq, Nurul Yahdi; Khusaini, Moh.; Hidayati, Bunga; Salah, Ahmad Khalid (Sekolah Pascasarjana Universitas Brawijaya, 2025)
The issue of sustainable development is a major challenge in regional development planning, including in Malang City. This study aims to evaluate the impact of increasing human resource capacity on the effectiveness of implementing the Sustainable Development Goals (SDGs), focusing on integrating strategic planning and developing the competencies of civil servants through a Corporate University approach. Using a quantitative method with Structural Equation Modeling (SEM-PLS) analysis techniques, this study analyzes the relationships between variables from data collected through a survey of civil servants in the Malang City Government. The results indicate that HR capacity building significantly contributes to achieving SDG targets. Furthermore, strategic planning and implementing the Corporate University approach are mediating variables that strengthen this relationship. This study highlights the importance of transforming the civil servant training system from a classical model to a sustainable and adaptive strategic learning system. These findings have policy implications for local governments in designing more targeted competency development strategies relevant to organizational needs and aligned with sustainable development agendas. Keywords: Corporate University, Human Resource Capacity, SDGs, Strategic Planning